Why devaluation : four broadcast talks (New Delhi Publication Division, Ministry of Information and Broadcasting, 1966)
These are talks broadcast from all India Radio by Shri Sachindra Chaudri (June 5, 1966), Shri Y.B. Chavan (June 8, 1966), Shri S.K. Patil (June 9, 1966) and Shrimati Indira Gandhi (June 12, 1966)
osc 12/4/17
Loans
Keywords: Devaluation; Foreign Exchange; India